2021
DOI: 10.35912/ijfam.v3i2.536
|View full text |Cite
|
Sign up to set email alerts
|

The financial impacts of board mechanisms on performance: The case of listed Moroccan banks

Abstract: Purpose: The present study examines the impact of corporate governance mechanisms on listed Moroccan banks' financial performance. Research methodology: This study investigates the relationship between listed banks' governance mechanisms and financial performance in the CSE for six years between 2014-2019. This study employs three performance measures, return on assets, return on equity, and Tobin's Q, to determine bank performance. This research uses the GMM EGLS approach to analyze data. In the first phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…The author shows that managerial commitment to the operations of the system and closely monitoring its implementation to the staff at all levels improves the control environment. However, (Idrissi & Alami, 2021) show that audit and nomination committees significantly affect financial performance while (Bayunitri & Nugraha, 2020) found that internal control significantly prevents fraud. Njagi and Mwangi (2019) established a significant correlation between control environment and revenue collection.…”
Section: Effect Of Control Environment On Financial Accountabilitymentioning
confidence: 99%
“…The author shows that managerial commitment to the operations of the system and closely monitoring its implementation to the staff at all levels improves the control environment. However, (Idrissi & Alami, 2021) show that audit and nomination committees significantly affect financial performance while (Bayunitri & Nugraha, 2020) found that internal control significantly prevents fraud. Njagi and Mwangi (2019) established a significant correlation between control environment and revenue collection.…”
Section: Effect Of Control Environment On Financial Accountabilitymentioning
confidence: 99%
“…Corruption may develop into threats, threats, and extortion from a public official or a customer. It takes place inside the government units in the private and public sectors or outside it (Al-Nawas & Abdul-Jabbar, 2015; Idrissi & Alami, 2021).…”
Section: Concept Of Corruptionmentioning
confidence: 99%
“…Today, the company must consider the impact of its activities on all its stakeholders in addition to generating profits on its own (Frimousse & Peretti, 2020). Accounting and/or market indicators can be used to measure financial performance (Aupperle, Carroll, & Hatfield, 1985); (McGuire, Sundgren, & Schneeweis, 1988); (Seifert, Morris, & Bartkus, 2004); (El Idrissi & Alami, 2021). Several authors have questioned CSR's ability to improve financial performance.…”
Section: Focus On Financial Performancementioning
confidence: 99%